PENDAMPINGAN GURU MENINGKATAN PEMAHAMAN TENTANG UNSUR – UNSUR LINGKARAN DENGAN MODEL PEMBELAJARAN BERBASIS PROYEK (PJBL) KELAS VI SD NEGERI GANTANG, PUJUT, LOMBOK TENGAH – NTB - Etika Ariyani; Baiq Titik Hendrawati (Bajang Institute, 2023)
The aims of this community service program was to help teacher improved students understanding about circle elements using project based learning at sixth grade students of SDN Gantang, Pujut, Central Lombok – West Nusa Tenggara Province. This study applied classroom action research which consists of four steps such as planning, implementation, observation and reflection. The results of this study shown that there is an improvement at students understanding. At the first cycle, there were 6 students (33,3 %) achieved mastery learning with an average level 65.56 then increased to 15 students (83,3 %) with an everage level 88.87. Based on the results of this study, it can be concluded that the implementation of project based learning can improved students understanding of mathematic learning about circle elements significantly in class VI students of SDN Gantang , Pujut, Central Lombok – West Nusa Tenggara